Efeito do enriquecimento ambiental sobre a ansiedade e morfologia neuronal de coelhos (Oryctolagus cuniculus) - Bozicovich, Thais Freitas Marques [UNESP] (2015)
The study was carried out with 56 rabbits from the Botucatu genetic group weaned at 35 days of age and followed up to 79 days of age. The objective was to evaluate the anxiety of growing rabbits using two types of enrichment: physical and social. The animals were assigned to a completely randomized design with a 2 x 2 factorial arrangement (with or without physical enrichment and with or without social enrichment), with four replicates. The animals with social enrichment were allocated six per cage in eight wire cages whereas the animals deprived of social contact were housed in eight individual wire cages. Galvanized sheets were adapted to the lateral parts of these cages to avoid the visual contact with other animals. Half the cages, randomly chosen, were enriched with eucalyptus sticks hung to the cage ceiling. The evaluation of anxiety was conducted using the elevated plus maze, through the locomotor activity and immobilization behaviors. The latency time to enter one of the arms, as well as the number of entries into and the time spent in each of the arms (open and closed) were recorded. Two observations were made, with the duration of 5 minutes each: the first at 49 and the second at 77 days of age. Growth performance was also assessed (average daily gain, feed consumption and feed conversion). The rabbits housed without social enrichment stayed longer both in the open and closed arms than the animals housed in groups. However, the later showed shorter latency to enter the open arms as well as to reach the end of the open arm, besides presenting a higher number of head dipping. Group-housed animals made more entries into the open arms when they were older than when they were younger. Isolated animals, on the other hand, showed the opposite response: a higher number of entries into the open arms when they were younger than when they were older. The rabbits in physically enriched environment show ...